The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.4041/kjod.2019.49.6.404
|View full text |Cite
|
Sign up to set email alerts
|

Bracket bonding to polymethylmethacrylate-based materials for computer-aided design/manufacture of temporary restorations: Influence of mechanical treatment and chemical treatment with universal adhesives

Abstract: ObjectiveTo assess shear bond strength and failure mode (Adhesive Remnant Index, ARI) of orthodontic brackets bonded to polymethylmethacrylate (PMMA) blocks for computer-aided design/manufacture (CAD/CAM) fabrication of temporary restorations, following substrate chemical or mechanical treatment.MethodsTwo types of PMMA blocks were tested: CAD-Temp® (VITA) and Telio® CAD (Ivoclar-Vivadent). The substrate was roughened with 320-grit sandpaper, simulating a fine-grit diamond bur. Two universal adhesives, Scotchb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…Normally, RUC is used as an adhesive resin cement in prosthodontic treatment, and it is more liquid than the traditional cement commonly used for orthodontic bracket, such as FLC and XT used in this study. Better physical mobility makes RUC better penetrate into the groove of the bracket bottom plate, thus forming better mechanical interlocking 33) .…”
Section: Discussionmentioning
confidence: 99%
“…Normally, RUC is used as an adhesive resin cement in prosthodontic treatment, and it is more liquid than the traditional cement commonly used for orthodontic bracket, such as FLC and XT used in this study. Better physical mobility makes RUC better penetrate into the groove of the bracket bottom plate, thus forming better mechanical interlocking 33) .…”
Section: Discussionmentioning
confidence: 99%
“…The Assure Plus company, whose popularity in adhesives has increased in recent years, 8 has claimed that Assure Plus is better at bonding than other adhesive systems both to enamel and restoration surfaces. 13,14 The originality of this study is that it evaluated the shear bond strength of orthodontic attachments on composite restoration surfaces in terms of both different surface treatments and different adhesive systems on extracted teeth. It is also one of the limited studies evaluating the bond strength of molar tubes in naturally extracted teeth with Assure Plus.…”
Section: Discussionmentioning
confidence: 99%
“…8 Although Assure Plus is a new adhesive, it has been reported that it is more effective in terms of shear bond strength in a limited number of studies in the literature. 13,14 However, since the product is new and the number of these studies is very limited, more evidence-based studies are needed.…”
Section: Introductionmentioning
confidence: 99%
“…With the aid of CAD/CAM systems, high-quality orthodontic treatment is expected to be achieved [ 29 , 30 ]. The accuracy of bracket transfer jigs has also increased as the technologies, especially CAD/CAM systems, have been developed.…”
Section: Discussionmentioning
confidence: 99%